The construction process of meme meaning among islamic youth in Malaysia - Anuar, Faizul Nizar; Yusuf, Sarina (Human Resource Management Academic Research Society, 2023)
Following the progress of technology that is growing today, it can be suggested that the process of delivering information has rapidly developed. Some messages are creatively produced in various forms including words, pictures, or videos. This situation further creates certain meanings in the recipient's thoughts. Hence, this study attempted to explore the process of constructing the meaning of memes among Muslim youth in Malaysia by referring to 30 memes. A total of 15 memes were obtained from Si Rashid's Facebook account and another 15 memes were obtained from the Gags Malaysia account. The meme sample was chosen as it recorded the highest number of likes in the period from 1 May 2018 to 30 July 2018. The qualitative method was applied by interviewing a total of 29 informants through focus group discussion (FGD). The results of this study found several processes involved in the construction of meaning that has taken place, including checking the validity and credibility of the information obtained. In addition, it was found that recipients will also relate to the memes they watched with their personal experiences, religious teachings, and the culture they practice. In addition, the findings of this study also discovered that the recipient would try to reflect on the memes they watched based on current issues that are happening or have happened.